Phenotypic approaches to gene mapping in platelet function disorders - Watson, S.; Daly, M.; Dawood, B.; Gissen, P.; Makris, M.; Mundell, S.; Wilde, J.; Mumford, A. (Hämostaseologie, 2010)
Platelet number or function disorders cause a range of bleeding symptoms from mild to severe. Patients with platelet dysfunction but normal platelet number are the most prevalent and typically have mild bleeding symptoms. The study of this group of patients is particularly difficult because of the lack of a gold-standard test of platelet function and the variable penetrance of the bleeding phenotype among affected individuals.The purpose of this short review is to discuss the way in which this group of patients can be investigated through platelet phenotyping in combination with targeted gene sequencing. This approach has been used recently to identify patients with mutations in key platelet activation receptors, namely those for ADP, collagen and thromboxane A2 (TxA2). One interesting finding from this work is that for some patients, mild bleeding is associated with heterozygous mutations in platelet proteins that are co-inherited with other genetic disorders of haemostasis such as type 1 von Willebrand‘s disease. Thus, the phenotype of mild bleeding may be multifactorial in some patients and may be considered to be a complex trait.
Keywords: Platelet dysfunction